The compressive stiffness of human pediatric heads. Issue 14 (5th November 2015) - Loyd, Andre Matthew; Nightingale, Roger W.; Luck, Jason F.; Song, Yin; Fronheiser, Lucy; Cutcliffe, Hattie; Myers, Barry S.; Dale Bass, Cameron R.
Abstract: Head injury is a persistent and costly problem for both children and adults. Globally, approximately 10 million people are hospitalized each year for head injuries. Knowing the structural properties of the head is important for modeling the response of the head in impact, and for providing insights into mechanisms of head injury. Hence, the goal of this study was to measure the sub-injurious structural stiffness of whole pediatric heads. 12 cadaveric pediatric (20-week-gestation to 16 years old) heads were tested in a battery of viscoelastic compression tests. The heads were compressed in both the lateral and anterior–posterior directions to 5% of gauge length at normalized deformation rates of 0.0005/s, 0.01/s, 0.1/s, and 0.3/s. Because of the non-linear nature of the response, linear regression models were used to calculate toe region (<2.5%) and elastic region (>2.5%) stiffness separately so that meaningful comparisons could be made across rate, age, and direction. The results showed that age was the dominant factor in predicting the structural stiffness of the human head. A large and statistically significant increase in the stiffness of both the toe region and the elastic region was observed with increasing age ( p <0.0001), but no significant difference was seen across direction or normalized deformation rate. The stiffness of the elastic region increased from as low as 5 N/mm in the neonate to >4500 N/mm in the 16 year old. The changes in stiffness with age may be attributed to the disappearance of soft sutures and the thickening of skull bones with age.